الصحافة الإصلاحية في الجزائر ودورها في بروز الوعي الوطني 1925-1954 - عيجولي, حمزة (جامعة الوادي - University of Eloued, 2022)
يعد الاتجاه الإصلاحي تيارا مهما ومتميزا من تيارات الحركة الوطنية الجزائرية، حيث كانت له رؤية خاصة في الإصلاح والتغيير والمواجهة مع الاستعمار الفرنسي، قوامها الأساسي إحياء الشخصية الجزائرية بمقوماتها الحضارية القائمة على الإسلام والعربية في ظل الانتماء إلى الوطن الجزائري الذي يختلف عن فرنسا وأطروحاتها الإدماجية والتغريبية. وقد كان للإصلاحيين وجمعية العلماء المسلمين الجزائريين كإطار جامع لهم، جرائد ومجلات ومنشورات تعبر عن لسان حالهم ومقالهم وتوضح مبادئهم وأهدافهم، فكانت تلك الوسائل الإعلامية بمثابة السلاح الفعال الذي تعتمد عليه الحركة الإصلاحية في الجزائر لنشر أفكارها والتعريف برسالتها، وبث الوعي في أوساط الجزائريين بما يخدم دينهم ولغتهم وقضيتهم الوطنية وانتمائهم الحضاري. The reformist trend is considered as an important and outstanding current in the Algerian nationalistmovement, in thatithad a specific perspective in the reformation, change and confrontation of the French colonialism, mainlybased on reviving the Algerian identity with its civilisational components that centre around Islam and Arabic, under the umbrella of an Algerian homeland, different from France and its westernizing and integrationistproposedplatforms. Reformists and the Association of Algerian MuslimUlemahad a unifying frame: newspapers, magazines and publications that express theirthought and explaintheirprinciples and goals. Mass media were an effective weapon on which the reformistmovementrelied to spreaditsideas, publicizetheir message, and spreadawarenessamong the Algerian population to serve theirfaith, and language; their national cause and theircivilisationalsense of belonging to .
مقال
Keywords: الحركة الإصلاحية – الصحافة الإصلاحية – جريدة المنتقد –جمعية العلماء المسلمين الجزائريين; reform movement-reformpress-Al MuntaqidNewspaper